Species Authentication and Sex Differentiation of Cattle and Buffalo Meat using Polymerase Chain Reaction and Restriction Fragment Length Polymorphism of Amelogenin XY Gene - Girish, P.S.; Vathiyanathan, S.; Bagale, Shailesh; Karabasanavar, Nagappa (Journal of Meat Science, 2016)
Production, consumption and export of cattle meat (beef) are restricted, while that of buffalo meat is permitted without much restriction in India. Guidelines for prevention of cow slaughter are more stringent as compared to that of bullocks/ bulls. This necessitates authentic species and sex detection tools. In the present study, a technique based on polymerase chain reaction –restriction fragment length polymorphism (PCR–RFLP) has been developed for simultaneous detection of species and sex of cattle and buffalo meats. Amelogenin XY genes pecific PCR yielded two amplicons of size 280 and 217 bp in males and a single amplicon of 280 bp size in females. Further, restriction digestion of purified 217 bp Amelogenin Y amplicon yielded two fragments of size 133 bp and 84 bp in buffalo only (uncut in cattle). Results revealed that PCR–RFLP XY gene can be a convenient and quick assay for sex and species differentiation of beef and buffalo meat.
Keywords: Beef; Buffalo meat; Speciation; Sexing; PCR